Pengaruh Sistem Pengendalian Internal Pemerintah dan Kompetensi Aparatur Sipil Negera terhadap Kecurangan Akuntansi - Hegi Renes; Novita Sari; Halimatusyadiah Halimatusyadiah; Baihaqi Baihaqi (Universitas Nusantara PGRI Kediri, 2026)
This study was conducted to analyze the influence of the Government Internal Control System (SPIP) and ASN competency on accounting fraud in the Regional Work Units (SKPD) of Mukomuko Regency. This study used a quantitative method with a survey approach. The study population was all SKPDs in Mukomuko Regency, with a sample of 48 SKPDs using a total sampling technique. Data were analyzed using multiple linear regression to determine the influence of SPIP and ASN competency on accounting fraud in SKPDs of Mukomuko Regency. The results showed that SPIP had a negative and significant effect on accounting fraud and ASN competency also had a negative and significant effect on accounting fraud in SKPDs of Mukomuko Regency. These findings confirm that increasing the effectiveness of SPIP and developing ASN competency, particularly in planning, technical skills, and documentation management, are key strategies in suppressing accounting fraud.